EXPLORING YOUNG LEARNERS TEACHERS COMPETENCY AND CHALLENGES IN TEACHING ENGLISH - Anggrarini, Natalia (Wiralodra English Journal, 2019)
Competency is a set of knowledge, skill and experience necessary for the future, which manifest in their activity (White, 1959). Teaching competency reflects how teacher?s ability in teaching and learning activity. Regarding to English teaching and learning to foreign learners, young learners are also exposed to have this language mastery. But Indonesian Government (see 2013 Curriculum of Elementary School) limits the subjects in Elementary School into six subjects and English is excluded. For some elementary schools, English is not give, but some others English is put as Local Content. The decision of local content here is based on the need of society, and it is happened in some elementary school in Indramayu. Thus, an English teacher for young learners in some elementary schools should reflect their competency in teaching English. She/he should be occupied with knowledge, skill and experience that needed to teach English to young learners so the purpose can meet the need. The aim of this research is to find out teaching competence of English teacher in teaching English to young learners. By conducting qualitative descriptive, this research uncovered the competency of teacher in planning the lesson, media and the implementation so it can be a consideration to put back English subject as one of main subjects in Elementary School. From the finding, it can be seen that some English teachers had made their efforts on performing good ability in teaching English such as in lesson planning, teaching media, teaching and learning activity and teaching assessment. While the challenges in teaching English to young learners were from students? behavior. The students? unawareness, unwillingness and laziness to study were the challenges of teaching English for young learners.